2017
DOI: 10.1080/00221546.2016.1272091
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Developmental Education Reform in Florida: A Policy Implementation Typology

Abstract: This study identified the policy perspectives of "street-level bureaucrats" in higher education (in this case, community college personnel) and linked them to a typology of 4 policy implementation patterns. The context for this qualitative study is state legislation in Florida (Florida Senate Bill 1720, 2013) that fundamentally reformed developmental education in the 28 state colleges (formerly community colleges) in the Florida College System (FCS). Study participants included 518 administrators, faculty, aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…Helping students get through their dev-ed requirements and gateway coursework has implications for students’ momentum toward a degree (Adelman, 2006; Calcagno, Crosta, Bailey, & Jenkins, 2007; Jenkins & Bailey, 2017). Stakeholders in higher education acknowledge the challenges posed by traditional dev-ed, and in response, several states have initiated dev-ed reforms (Brower, Bertrand Jones, Tandberg, Hu, & Park, 2017; Edgecombe, Cormier, Bickerstaff, & Barragan, 2013). In this section, we describe the potential solutions, including components of ongoing reforms used across the country.…”
Section: Updating Dev-ed In Mathematicsmentioning
confidence: 99%
“…Helping students get through their dev-ed requirements and gateway coursework has implications for students’ momentum toward a degree (Adelman, 2006; Calcagno, Crosta, Bailey, & Jenkins, 2007; Jenkins & Bailey, 2017). Stakeholders in higher education acknowledge the challenges posed by traditional dev-ed, and in response, several states have initiated dev-ed reforms (Brower, Bertrand Jones, Tandberg, Hu, & Park, 2017; Edgecombe, Cormier, Bickerstaff, & Barragan, 2013). In this section, we describe the potential solutions, including components of ongoing reforms used across the country.…”
Section: Updating Dev-ed In Mathematicsmentioning
confidence: 99%
“…An example of theory-building from the DE reform project was a qualitatively derived typology of four broad policy implementation patterns (oppositional, circumventing, satisficing, and facilitative implementation) developed in conjunction with 14 specific behaviors such as improvising and leaving the institution (Brower et al, 2017). An empirically grounded typology, or classification of a social phenomenon according to type, can be derived from qualitative data using methods such as those developed by Kluge (2000).…”
Section: What Opportunities and Constraints Are Presented By Samplingmentioning
confidence: 99%
“…Big qual can also be aligned with "rapid qualitative inquiry" (Beebe, 2014) and "multi-sited ethnography" (Coleman & von Hellermann, 2011), though we include in our definition both "slow" and "rapid" methods and qualitative traditions beyond ethnography including, for instance, case study, narrative inquiry, and grounded theory. Our review revealed that the most common research tradition for big qual was the case study (e.g., Brower et al, 2017;Calma, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Implementasi kebijakan pendidikan melibatkan proses penterjemahan (translate) kebijakan kedalam kebijakan prosedural, peraturan atau instrumen administratif (Gilson, 2016). Tahapan implementasi merupakan fase kritis terhadap efektivitas sebuah kebijakan (Brower, 2017). Implementasi kebijakan pendidikan adalah bagaimana kebijakan diterjemahkan di sekolah dan kelas (Swanson, 2007).…”
Section: Jurnal Administarsi Pendidikanunclassified